2011
DOI: 10.5306/wjco.v2.i11.367
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor receptor and K-Ras in non-small cell lung cancer-molecular pathways involved and targeted therapies

Abstract: Lung cancer is currently the leading cause of cancer death in Western nations. Non-small cell lung cancer (NSCLC) represents 80% of all lung cancers, and adenocarcinoma is the predominant histological type. Despite the intensive research carried out on this field and therapeutic advances, the overall prognosis of these patients remains unsatisfactory, with a 5-year overall survival rate of less than 15%. Nowadays, pharmacogenetics and pharmacogenomics represent the key to successful treatment. Recent studies s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 101 publications
(225 reference statements)
1
41
0
3
Order By: Relevance
“…So, based on these mechanisms, K-ras mutations, EGFR (also related to phosphorylation and tyosine kinase) mutations, copy number, and expression, should be better molecular biomarkers for patient selection Hassanein et al, 2012). In clinical medicine, there are also other markers such as COX-2, p53 (de Mello et al, 2011).…”
Section: Mapk and Lung Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…So, based on these mechanisms, K-ras mutations, EGFR (also related to phosphorylation and tyosine kinase) mutations, copy number, and expression, should be better molecular biomarkers for patient selection Hassanein et al, 2012). In clinical medicine, there are also other markers such as COX-2, p53 (de Mello et al, 2011).…”
Section: Mapk and Lung Cancermentioning
confidence: 99%
“…In other experiments, by knocking down and over-expression of EAPII in NSCLC, C Li.et.al found that EAPII significantly affected Raf1 and ERK1/2 (important composition of the MAPK signal pathway) and during the process, the MAPK-ERK pathway which elevates levels of MYC and cyclin D1 was activated. In their hypothesis, EAPII has an oncogenic role in lung cancer development (Li et al, 2011a), As for the Ras/MAPK pathway, EGFR protein activates both K-Ras 4B and H-Ras in different ways, and affects nuclear transcription of several downstream genes in a GTP-dependent way (de Mello et al, 2011).…”
Section: Mapk and Lung Cancermentioning
confidence: 99%
“…These intracellular signaling pathways essentially channel the signal emanating from the cell surface into the nucleus, where they modulate transcription of genes involved in key cellular functions, including cell survival (antiapoptosis), proliferation, angiogenesis, invasion, and metastasis. 5 Mutations in the gene encoding proteins involved in EGFR signaling cascade (KRAS, HER2/neu, BRAF, P13K, LKB1, and SHP2) are mutually exclusive somatic mutations, with the exception of P13K.…”
Section: Epidermal Growth Factor Receptormentioning
confidence: 99%
“…Mutant EGFRs (either by exon 19 deletion or punctual mutation in exon 21 known as L858R) show an increased amount and duration of EGFR activation compared with wild-type receptors [18]. Mutated EGFR can activate RAS/RAF/MEK/MAPK and phosphoinositide 3-kinase (PI3K)/AKT and STAT3/STAT5 pathways [19][20][21]. Beside the importance of EGFR on lung carcinogenesis, some other molecules have been described as molecular markers for prognosis and therapeutic targets.…”
Section: Genome Biomarkers: the Opening To Personalized Medicine In Lmentioning
confidence: 99%